New Education Policy 2020 on Higher Education (Journal of Advances and Scholarly Researches in Allied Education, 2024)
The development of an equitable and justice society, the realization of individual potential, and the advancement of national development all depend on education. Providing universal access to quality education is the key to India’s continued ascent, and leadership on the global stage in terms of economic growth, social justice and equality, scientific advancement, national integration, and cultural preservation. The historic and self-proclaimed new national education policy 2020 was unveiled on July 29, 2020. It covers every facet of education in the modern era with an eye toward the future. To actively contribute to the transformation of the nation into a society of equal, sustainable, and healthy knowledge. The National Education Policy 2020 examines the Indian educational system with an emphasis on its traditions, customs, values, and morals. India's education system is still being developed, with entries from his extensive and lengthy past and contributions from numerous scholars worldwide in a range of subjects like astronomy, metalworking, mathematics, medical and surgical science, crafts, architecture, yoga, fine arts, and so forth. The current NEP 2020 objective is to raise the current enrollment rate by offering open, multidisciplinary education to everyone who wants it. The objective of the paper is to focus on the main features of NEP-2020 and its impact on Higher Education.